The Distribution of Verb Tenses and Modal Verbs in Life Today: A Corpus-Based Analysis of Phase F English Textbooks - Fallianda, Fallianda (Lingua Susastra, 2025)
This study investigates the distribution of verb tenses and modal verbs in Phase F English textbooks in Life Today textbook using a corpus-based approach. A self-compiled mini-corpus was constructed from four textbook units representing narrative, argumentative, hortatory exposition, and discussion texts. The corpus consists of reading passages, selected listening and video transcripts provided in the teacher’s handbook, with the total of 10,438 unigram tokens and 2,736 unigram types. Corpus analysis was conducted using AntConc 4.3.1, focusing on frequency and dispersion patterns of the 100 highest- occurrence of verb forms, modal auxiliaries, and particular lexical verbs. The findings indicate that the language input reflects genre-specific grammatical patterns, for example the dynamic tense variation characteristic of narrative texts or the grammar complexity and lexical variation in discussion texts. However, discrepancies are identified between the grammatical patterns evidenced in the corpus and the explicit language features presented in the textbook, particularly in terms of grammatical scaffolding and the progression of text complexity across units. These findings highlight the need for more explicit and corpus-informed grammatical scaffolding to support genre-based language learning and to enhance the development of students’ receptive and productive skills at the senior secondary level.